2007
DOI: 10.1002/chem.200701001
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Asymmetric Conjugate Addition of Trialkylaluminium Reagents to Trisubstituted Enones: Construction of Chiral Quaternary Centers

Abstract: Me3Al, Et3Al, and vinylalane species undergo enantioselective conjugate addition to a wide range of 2- or 3-substituted enones (cyclopent-2-enones, cyclohex-2-enones, 3-methyl cyclohept-2-enone) in the presence of catalytic amount of copper salt (copper thiophene carboxylate, [Cu(CH3CN)4]BF4 or [CuOTf]2C6H6) and tropos-phosphoramidite-based ligand. Thus, chiral quaternary centers can be built, with up to 98% ee after rigorous optimization of experimental conditions. It was shown that the main important paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 68 publications
2
104
0
4
Order By: Relevance
“…The following compounds were attained by literature procedures: 1 a, [11] 1 b, [12] L A , [17] 2 a, [14] 11, [12] and L D . [23] Alternative preparation of 1 b-c 2-Formyl-1,3-dithiane (2 a): [14] To a flame-dried flask containing 1,3-dithiane (2.50 g, 20.8 mmol) in dry THF (50 mL) at À30 8C nBuLi (14.0 mL, 1.6 m in hexane, 22.4 mmol) was added and the reaction mixture was stirred at this temperature for 1 h. The mixture was allowed to come to À10 8C and dry N,N-dimethylformamide (560 mL, 7.21 mmol) was added. The mixture was stirred for 2 h at À10 8C before warming to 0 8C and overnight stirring at room temperature.…”
Section: Methodsmentioning
confidence: 97%
“…The following compounds were attained by literature procedures: 1 a, [11] 1 b, [12] L A , [17] 2 a, [14] 11, [12] and L D . [23] Alternative preparation of 1 b-c 2-Formyl-1,3-dithiane (2 a): [14] To a flame-dried flask containing 1,3-dithiane (2.50 g, 20.8 mmol) in dry THF (50 mL) at À30 8C nBuLi (14.0 mL, 1.6 m in hexane, 22.4 mmol) was added and the reaction mixture was stirred at this temperature for 1 h. The mixture was allowed to come to À10 8C and dry N,N-dimethylformamide (560 mL, 7.21 mmol) was added. The mixture was stirred for 2 h at À10 8C before warming to 0 8C and overnight stirring at room temperature.…”
Section: Methodsmentioning
confidence: 97%
“…In a previous report, Alexakis and co-workers have demonstrated that copper-catalyzed conjugate addition of Grignard reagents onto α-methyl cyclic enones, affording mainly the trans -2,3-disubstituted cyclohexanones as being the thermodynamic products [52]. Similarly, we believe that the intramolecular conjugate addition of carbanion 3j onto α-substituted enone moiety is under thermodynamic control, leading to the tricyclic compound 6j , in which the two hydrogens H 2 and H 3 , are on a trans -ring junction whereas the second ring junction is cis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The second reaction, formation of phosphoramidite 3, was reported to proceed in THF (Vuagnoux-d'Augustin et al;www.ccsenet.org/ijc International Journal of Chemistry Vol. 8, No.…”
Section: Resultsmentioning
confidence: 99%
“…A series of chiral ligands have been prepared, particularly the preparation of ligand 3 has been described in the literature (Vuagnoux-d'Augustin et al;2007) and is shown in Scheme 1. This ligand was used in the copper mediated asymmetry-inducing step in a production of taxadienone (Mendoza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%